Pasivos ambientales sobre el recurso agua en el Humedal la Segua generados por actividades productivas - Intriago Zambrano, Gissela Karolina (2024)
The purpose of the research was to evaluate the environmental liabilities on the water resource in the La Segua Wetland generated by productive activities in the communities La Sabana, Larrea (Tosagua) and La Segua, San Antonio (Chone). The exploration and observation tour of the wetland was carried out, applying an identification card that was verified in 3 environmental liabilities: the drainage of the Chone River channel (D.C.R.C.) and 2 shrimp pools "Párraga (P.C.P.) and Mendoza (P.C.M.)"; and with the help of the surveys, it was obtained that 100% of the respondents want these activities to be environmentally friendly. In addition, liabilities were measured through an importance matrix, where the 3 recognized liabilities (D.C.R.C; P.C.P. and P.C.M) were rated severe-critical. For each passive, 2 samples were taken to comply with the respective physicochemical analyses: electrical conductivity, DBO5, DQO, NO2, NO3, pH and NTU; As for nitrites, in all the levels of contamination identified, they exceeded the maximum permissible limits of Ministerial Agreement 097-A, and the pH value is close to the limits of station 2 of the effluent from the Mendoza shrimp pool. The remaining parameters are within the established limits. Therefore, 3 corrective measures were recommended for each liability, through phytoremediation and natural coagulation strategies, to mitigate and reduce their environmental impact.